EXPRESSION ANALYSIS WITH SOCIO EMOTION ATTITUDE IN SINGING ACTIVITY OF 5-6-YEAR-OLD CHILDREN - Fachriyyati, Dyah; Hartono, Hartono; Susilaningsih, Endang (Journal of Primary Education, 2020)
The process of singing is related to the social process of the child's emotions with the environment, and the social process of emotions involves changes in one's relationships with others, changes in emotions and personalities. This research aims to analyze the singing expression of children in the teaching and learning process at Tarbiyatul Athfal Kindergarten, Krapyak, Jepara. The subjects consisted of early childhood students in Class B or within 5-6-year-old age interval at Tarbiyatul Athfal Kindergarten by taking 3 classes in which each of them represented by 3 students of each category. Thus, there were 9 students taken as the subjects. The research methodology was a qualitative approach. Examine the child's expression when singing in the learning process, how the teacher's role in leading and directing the learning process and see how the child's expression is produced from singing. The findings concerning the singing expression of the children were each child had different expressions while singing. Each expression showed different socio-emotional attitudes. Some students indifferently accepted the song as learning media. Thus, they seemed sufficiently active in learning. In contrast, children were not interested in the song. It showed that children were less active in receiving a lesson from the teacher. The research conclusion shows three student categories in learning. They are (1) active students in learning when singing activities that children are always cheerful, excited and complete their assignments according with their teacher?s directions (2) sufficiently active students, the children are less cheerful and excited, their body?s movement is very limited, so it can affect in their enthusiasm to complete the assignments, (3) less active students in learning, children are not at all interested in the songs provided, they have their world that they like. The research benefits are as reference for further researchers to find out student categories in learning which is adjusted to the obtained expression while singing and having socio-emotional attitudes obtained from the activity.